Efektivitas Model Pembelajaran Problem Based Learning terhadap Kemampuan Literasi Ekologi Siswa Kelas X Sekolah Menengah Atas - Latif Agung Nugroho; Baskoro Adi Prayitno; Puguh Karyanto (Jurnal Konseling dan Pendidikan, 2018)
The purpose of the study is investigating the effect of problem based learning on students’ ecological literacy, comparing problem based learning with traditional teaching method. Quasi experimental research design included 60 students (30 experimental, 30 control group) in 10 grade senior high school in Surakarta. The experimental group was taught using the problem based learning while the control group was taught using the traditional approach. The control and the experiment group have been determined randomly. The data were collected using ecological literacy scale. The data has been analyzed by using statistical analysis techniques. Independent sample t-test was used for data analysis with SPSS 18.0. The results of the study showed that the problem based learning method was more effective in improving the ecological literacy skills of students compared to the traditional method.